(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The cited reaction has been studied at 298 K by gasometric method. At 0.5 ⋅10-2≤[DMSO]0 ≤4 ⋅10-2 M the reaction rate (RO2) is being increased approximately by 16%. It is established by ESR method that TEMPO is not being expended and does not influence on the RO2. In DMSO presence the reaction activation energy is less by 5.4 kJ/mol. It is assumed that H2O2 molecule interacts with the polar O^δ −← S (CH3)2^δ + bond of DMSO molecule, which results in activation of H2O2 molecule. It reacts with enhanced rate HOO– anion by nonradical mechanism. A mechanism is proposed and discussed.